Melanoma Unknown Primary Brain Metastasis Treatment with ECHO-7 Oncolytic Virus Rigvir: A Case Report - Proboka, Guna; Tilgase, Andra; Isajevs, Sergejs; Rasa, Agnija; Alberts, Pēteris (Frontiers in Oncology, 2018)
Melanoma is considered an aggressive malignancy with a tendency for forming metastasis in the brain. Less than 10% of all melanoma cases present with unknown primary tumor location. This diagnose is yet to be fully understood, because there are only theoretical assumptions about the nature of this disease. Melanoma brain metastases have many severe side effects and unfortunately, any disease related to the brain has limited therapeutic options due to the blood brain barrier. The course of the disease after completing a treatment course, and stopping the treatment, is complicated to predict and is difficult to obtain long-lasting remission. In this report we describe a female patient with unknown primary melanoma brain metastasis being treated with the oncolytic ECHO-7 virus Rigvir® after brain surgery. The patient has been stable, as monitored by MRI, for more than 3 years with the therapy still ongoing. The median expected overall survival from the time of diagnosis is approximately five months. Additional positive effect could have been gained from use of the intranasal administration route, which is considered effective due to the direct anatomical connection between the nasal cavity and the central nervous system. However, further studies are required to fully understand this mode of drug administration.